(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The adsorption of levafix red (LR) dye from waste water via batch adsorption onto treated jute stick powder was investigated. Studies concerning the factors influencing the adsorption such as adsorbent dosage, pH, contact time and temperature were systematically investigated and discussed. The results revealed that the maximum removal of levafix red was 91% from water. The kinetics data were analyzed using pseudo-first order and pseudo-second order models. It was best described by the pseudo-second order model. The adsorption equilibrium follows Langmuir isotherm. This result indicates that treated jute stick powder could be employed as low-cost alternatives to commercial activated carbon for the removal of levafix red (LR) from waste water. Rapid industrialization in Bangladesh has resulted in increased water pollution that has higher dye level. Waste water from dyeing and finishing factories is a significant source of environmental pollution. The waste water is typically characterized by high levels of COD (chemical oxygen demand) concentration, high concentration of coloring material, large amount of suspended solids, highly fluctuating pH and high temperature. Dyes may therefore present an ecotoxic hazard and introduces the potential danger of bioaccumulation that may eventually affect man by transport through the food chain. As pharmaceutical industries use lots of water and intake of this type of water might have adverse effects on human health. Therefore, water purification is extremely essential for human and animal health and dye free water may be farther purified for its proper use. Bangladesh Pharmaceutical Journal 19(1): 75-84, 2016